Characterization of physiological and antioxidant responses in Run1Ren1 Vitis vinifera plants during Erysiphe necator attack - Sosa-Zuniga, Viviana; Martínez-Barradas, Vera; Espinoza, Carmen; Tighe-Neira, Ricardo; Valenzuela, Álvaro Vidal; Inostroza-Blancheteau, Claudio; Arce-Johnson, Patricio (Frontiers in Plant Science, 2022)
Grapevine is a fruit crop of major significance worldwide. Fungal attacks are one of the most relevant factors affecting grapevine yield and fruit quality, and powdery mildew caused by Erysiphe necator is one of the most harmful fungal diseases for this fruit-bearing species. Incorporating resistance genes such as Run1 and Ren1 in new vine selections offers a sustainable alternative to control the disease. These combined loci produce an immune response that prevents the development of the disease. However, to date studies are lacking concerning whether this response generates alterations in the physiological and antioxidant parameters of resistant plants in the presence of the fungus or if it has an associated energy cost. Therefore, the main goal of our research was to determine if Run1Ren1 plants present alterations in their physiological and biochemical parameters in the presence of the fungus. To achieve this target, a previously characterized resistant Run1Ren1 genotype and the susceptible Carménère cultivar were analyzed. We evaluated photochemical parameters (Fv’/Fm’, ΦPSII and ETR), net photosynthesis (Pn), photosynthetic pigments, transpiration (E), stomatal conductance (gs), oxidative stress parameters (MDA), antioxidant activity, and phenols. Our results show that the physiological parameters of Run1Ren1 plants were not negatively affected by the fungus at 10 days post-inoculation, contrasting with alterations observed in the susceptible plants. Therefore, we propose that the resistance response triggered by Run1Ren1 is physiologically and biochemically advantageous to grapevines by preventing the development of powdery mildew infection.